Wady systemowe w ochronie zdrowia jako zagrożenie sukcesu komercjalizacji i prywatyzacji opieki zdrowotnej w Polsce - Młodzianowska, Dorota (System Faults in Health Care as a Threat for the Successful Commercialization and Privatization of Health Service in Poland, 2006)
In view of the growing inefficiency of the Polish health care system, commercialization and privatization of health care providers seemed likely to secure improvement in the field of the medical care. However, it is alleged that due to the lack of identification of faults within the health care system itself, the processes of commercialization and privatization might fail despite careful planning and the proper process of their implementation. Apart from this, it can lead to further decrease in the system efficiency. On the grounds of the initial diagnosis of threats it could be possible to rationalize actions aiming at creating conditions for health care partnership of public and private providers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 29-41